2020
DOI: 10.1016/j.biopha.2020.110641
|View full text |Cite
|
Sign up to set email alerts
|

Lianhua Qingwen prescription for Coronavirus disease 2019 (COVID-19) treatment: Advances and prospects

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 33 publications
0
32
0
3
Order By: Relevance
“…However, no interaction was highlighted with the active site of the HCV helicase (Kaneez et al 2014). In SARS-CoV-2 context, Lianhua Qingwen Capsule (LQC) showed some therapeutic effects on Covid-19 patients (Li et al 2020). In view to understand the molecular mechanism of such activity, docking analysis has been executed with Autodock Vina (Xia et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, no interaction was highlighted with the active site of the HCV helicase (Kaneez et al 2014). In SARS-CoV-2 context, Lianhua Qingwen Capsule (LQC) showed some therapeutic effects on Covid-19 patients (Li et al 2020). In view to understand the molecular mechanism of such activity, docking analysis has been executed with Autodock Vina (Xia et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…LH capsules have re-attracted attention due to their effectiveness against COVID-19; specifically, these capsules can inhibit SARS-COV-2 replication and regulate the secretion of inflammatory cytokines( Li et al, 2020b ). Experiments using chicken embryos and cytotoxicity assays have shown that LH capsules are safe, and modern pharmacological studies have demonstrated that LH capsules exert a good inhibitory effect on influenza A virus (IAV) and influenza B virus (IBV)( Ding et al, 2017 ; Zhao et al, 2014 ).…”
Section: Safety and Effectiveness Of Lh Capsulesmentioning
confidence: 99%
“…[ 11 ] Chinese herbal injections were recommended for the treatment of COVID-19 after the outbreak of COVID-19 officially in China. [ 86 ] Up to now, cumulative clinical research progress has demonstrated the synergistic benefits of Chinese herbal injections in combination with Western medicine on reducing the time of SARS-CoV-2 RNA clearance, increasing the improvement rate of chest CT manifestations, as well as improving multiple other clinical outcomes ( Table 2 ). The pharmacological mechanisms mainly attributed to the antiviral activity, regulation of immunity, and inhibition of inflammatory storm.…”
Section: Future Perspectives and Concluding Remarksmentioning
confidence: 99%